Prevalence of common chronic disease and multimorbidity patterns in Guangdong province with three typical cultures: analysis of data from the Diverse Life-Course Cohort study - Hu, Yaoda; He, Huijing; Ou, Qiong; Nai, Jing; Pan, Li; Chen, Xingming; Tu, Ji; Zeng, Xuejun; Pei, Guo; Wang, Longlong; Lin, Binbin; Liu, Qihang; et al. (Frontiers in Public Health, 2023)
Background Variations in the prevalence and pattern of multimorbidity might be attributable to lifestyle and environmental factors. This study was performed to determine the prevalence of common chronic diseases and to reveal multimorbidity patterns among adults in Guangdong province with Chaoshan, Hakka, and island culture. Methods We used data collected at the baseline survey (April–May 2021) of the Diverse Life-Course Cohort study and included 5655 participants aged ≥20 years. Multimorbidity was defined as the presence of two or more of the 14 chronic diseases collected by self-reports, physical examinations, and blood tests. Multimorbidity patterns were explored by association rule mining. Results Overall, 40.69% of participants had multimorbidity, and the prevalence among coastland (42.37%) and mountain residents (40.36%) was higher than that among island residents (37.97%). The prevalence of multimorbidity increased rapidly with age and had an inflection point at 50 years, beyond which >50% of middle-aged and older adults had multimorbidity. The proportion of people with two chronic diseases accounted for most cases of multimorbidity, and the strongest association was found between hyperuricemia and gout (lift of 3.26). The most prevalent multimorbidity pattern was dyslipidemia and hyperuricemia in coastland areas and dyslipidemia combined with hypertension in mountain and island areas. Furthermore, the most common triad combination consisted of cardiovascular diseases, gout, and hyperuricemia, which was verified in mountain and coastal areas. Conclusion These observations of multimorbidity patterns, including the most frequent comorbidities and associations, will help healthcare providers to develop healthcare plans that improve the effectiveness of multimorbidity management.